A National Study Links Nurses' Physical and Mental Health to Medical Errors and Perceived Worksite Wellness. Issue 2 (February 2018) - Melnyk, Bernadette Mazurek; Orsolini, Liana; Tan, Alai; Arslanian-Engoren, Cynthia; Melkus, Gail D'Eramo; Dunbar-Jacob, Jacqueline; Rice, Virginia Hill; Millan, Angelica; Dunbar, Sandra B.; Braun, Lynne T.; Wilbur, JoEllen; Chyun, Deborah A.; et al.
Abstract : Objective: The aim of this study was to describe (1) nurses' physical and mental health; (2) the relationship between health and medical errors; and (3) the association between nurses' perceptions of wellness support and their health. Methods: A cross-sectional descriptive survey was conducted with 1790 nurses across the U.S. Results: Over half of the nurses reported suboptimal physical and mental health. Approximately half of the nurses reported having medical errors in the past 5 years. Compared with nurses with better health, those with worse health were associated with 26% to 71% higher likelihood of having medical errors. There also was a significant relationship between greater perceived worksite wellness and better health. Conclusion: Wellness must be a high priority for health care systems to optimize health in clinicians to enhance high-quality care and decrease the odds of costly preventable medical errors. Abstract : Supplemental Digital Content is available in the text